Effect of trypsin, kallikrein and kontrikal on the enzyme activity and cationic protein content of the blood neutrophils - Kharchenko, V Z; Protsenko, V A; Shpak, S I; Kolbasin, P N (Farmakologiia i toksikologiia, 1986)
It was shown on Wistar rats that trypsin and kallikrein decrease the activity of lactate dehydrogenase, alpha-glycerophosphate dehydrogenase, glycogen content and increase the activity of succinate dehydrogenase in neutrophils.